PENGARUH ETIKA PROFESI, PENGETAHUAN, PENGALAMAN, DAN INDEPENDENSI TERHADAP AUDITOR JUDGEMENT PADA BADAN PEMERIKSA KEUANGAN (BPK) PERWAKILAN SUMATERA SELATAN - Ranggi Armanda; Ubaidillah . (Program Studi Magister Manajemen FE Unsri, 2014)
This research is aimed at identifying the influence of work ethic, knowledge, experience, and interpendence on the auditors’ judgement at the Financial Audit Office of South Sumatera. This research uses a quantitative method and data are computed using SPSS 16.0. The sample consists of 34 auditors working in financial audit office of south sumatera. The primary data are collected from questionnaires. The research results show that work ethic, knowledge, experience, and interpendence simultaneously have a significant influence on the auditors’ judgement, that is, as much as 78%. This suggest show that the work ethic, knowledge, experience, and interpendence has significant impact on the auditors’ judgement at the financial audit office of south sumatera.